Olive oil consumption and all-cause, cardiovascular and cancer mortality in an adult mediterranean population in Spain - Torres-Collado, Laura; García-de la Hera, Manuela; Lopes, Carla; Compañ-Gabucio, Laura María; Oncina-Cánovas, Alejandro; Notario-Barandiaran, Leyre; González-Palacios, Sandra; Vioque, Jesús (Frontiers in Nutrition, 2022)
Objective We assessed the association between usual olive oil consumption (OOC) and all-cause, cardiovascular (CVD) and cancer mortality in an adult population in Spain. Materials and methods OOC was evaluated at baseline in 1,567 participants aged 20 years and older from the Valencia Nutrition Study in Spain using validated food frequency questionnaires. During an 18-year follow-up period, 317 died, 115 due to CVD and 82 due to cancer. Cox regression models were used to estimate adjusted hazard ratios (HR) and 95% confidence intervals (95%CI). Results After adjusting for demographic and lifestyle factors, the OOC was associated with a lower risk of all-cause, CVD and cancer mortality. Compared to the less than once per month consumption, the consumption of up to one tablespoon per day was associated with a 9% lower risk of all-cause mortality (HR: 0.91; 95%CI: 0.68-1.22) and the consumption of 2 or more tablespoons with a 31% lower risk of all-cause mortality (HR: 0.69; 95%CI: 0.50–0.93; p-trend = 0.011). The consumption of 2 or more tablespoons per day was also associated with lower risk of mortality for CVD (HR: 0.54; 95%CI: 0.32–0.91; p-trend = 0.018) and cancer (HR: 0.49, 95%CI: 0.26–0.94; p-trend = 0.019). Conclusion Higher olive oil consumption was associated with lower long-term risk of all-cause, CVD and cancer mortality in an adult Mediterranean population. The maximum benefit was observed for the consumption of two or more tablespoons per day.